Chronic inflammation decreases HSC fitness by activating the druggable Jak/Stat3 signaling pathway - Grusanovic, Srdjan; Danek, Petr; Kuzmina, Maria; Adamcova, Miroslava K; Burocziova, Monika; Mikyskova, Romana; Vanickova, Karolina; Kosanovic, Sladjana; Pokorna, Jana; Reinis, Milan; Brdicka, Tomas; Alberich-Jorda, Meritxell (EMBO reports, 2023)
Chronic inflammation represents a major threat to human health since long-term systemic inflammation is known to affect distinct tissues and organs. Recently, solid evidence demonstrated that chronic inflammation affects hematopoiesis; however, how chronic inflammation affects hematopoietic stem cells (HSCs) on the mechanistic level is poorly understood. Here, we employ a mouse model of chronic multifocal osteomyelitis (CMO) to assess the effects of a spontaneously developed inflammatory condition on HSCs. We demonstrate that hematopoietic and nonhematopoietic compartments in CMO BM contribute to HSC expansion and impair their function. Remarkably, our results suggest that the typical features of murine multifocal osteomyelitis and the HSC phenotype are mechanistically decoupled. We show that the CMO environment imprints a myeloid gene signature and imposes a pro-inflammatory profile on HSCs. We identify IL-6 and the Jak/Stat3 signaling pathway as critical mediators. However, while IL-6 and Stat3 blockage reduce HSC numbers in CMO mice, only inhibition of Stat3 activity significantly rescues their fitness. Our data emphasize the detrimental effects of chronic inflammation on stem cell function, opening new venues for treatment.
Keywords: chronic multifocal osteomyelitis; Animals; zánět; Osteomyelitis; niche; Hematopoietic Stem Cells; STAT3 Transcription Factor; lidé; osteomyelitida; Mice; signální transdukce; Interleukin-6; chronic inflammation; Signal Transduction; myši; Inflammation; Hematopoiesis; transkripční faktor STAT3; hematopoetické kmenové buňky; interleukin-6; IL-6/Jak/Stat3; hematopoéza; zvířata; hematopoietic stem cells; Humans